Analysis on the Effects of Hard Shading Pattern to I-V Performance Curve - Mohd Azlan, Ismail; Nur Lyana Jasmin, Adil; Farm, Yan Yan; Nazrein, Amaludin; Nur Amalina, Bohari; Sherena, Sar‑ee (Springer Nature Switzerland AG., 2023)
Hard shading on a photovoltaic (PV) module has a disproportionate impact on its power production. Minimizing power losses is critical in the installation of the PV module since it can greatly diminish the module’s performance and capacity to generate electricity. Thorough examination of the consequences of hard shading on the PV modules is necessary to lower power losses and maximize the module’s efficacy. This paper presents the background and findings from three different types of PV module (Full Cell, Half-Cut and Shingle PV module) operated under a variety of shading pattern (horizontal, vertical, and diagonal), and percentage (25%, 50%, and 75%). Experiments are conducted in a location at Sabah, a state located within Malaysia. Sabah which has a tropical climate with high temperatures and humidity, along with consistent level of solar radiation throughout the year making it well-suited for solar energy production. The experimental technique, which involved testing PV modules under various shading patterns and percentages, was found to be highly accurate in determining the amount of shading loss, particularly in instances of hard shading. The findings are presented by I-V and P-V curve that was traced by using a portable PV power meter (SEAWARD PV200) relating the pattern and percentage of shading to maximum power point (MPP) and power losses of the PV modules.